Big data : does size matter? - Harkness, Timandra (London, UK : Bloomsbury Sigma, 2016)
'Timandra Harkness cuts through the hype to put data science into its real-life context using a wide range of stories, people, and places to reveal what is essentially a human science--demystifying big data, telling us where it comes from and what it can do.'Big Data' then asks the awkward questions: What are the unspoken assumptions underlying its methods? Are we being bamboozled by mega data's size, its speed, and its shiny technology? Nobody needs a degree in computer science to follow Harkness's exploration of what mega data can do for us--and what it can't or shouldn't.'Big Data' asks you to decide: Are you a data point, or a human being?'--Provided by publisher.
Big data knows where you've been and who your friends are. It knows what you like and what makes you angry. It can predict what you'll buy, where you'll be the victim of crime and when you'll have a heart attack. Big data knows you better than you know yourself, or so it claims. But how well do you know big data? You've probably seen the phrase in newspaper headlines, at work in a marketing meeting, or on a fitness-tracking gadget. But can you understand it without being a Silicon Valley nerd who writes computer programs for fun? Yes, you can. Timandra Harkness writes comedy, not computer code. The only programs she makes are on the radio. If you can read a newspaper, you can read this book. Starting with the basics--what IS data? And what makes it big?--Timandra takes you on a whirlwind tour of how people are using big data today: from science to smart cities, business to politics, self-quantification to the Internet of Things. Finally, she asks the big questions about where it's taking us; is it too big for its boots, or does it think too small? Are you a data point or a human being? Will this book be full of rhetorical questions? No. It also contains puns, asides, unlikely stories and engaging people, inspiring feats and thought-provoking dilemmas. Leaving you armed and ready to decide what you think about one of the decade's big ideas: big data.--From dust jacket.
Part 1: What is it? Where did it come from?. What is data? And what makes it big? ; Death and taxes. And babies ; Thinking machines -- Part 2: What has big data ever done for us?. Big business ; Big science ; Big society ; Data-driven democracy -- Part 3: Big ideas?. Big Brother ; Who do we think you are? ; Are you a data point or a human being? -- Appendix. Keeping your data private.
Includes index.
Keywords: Big data -- Popular works